2019
DOI: 10.22610/jebs.v11i1(j).2752
|View full text |Cite
|
Sign up to set email alerts
|

The Contribution of Foreign Direct Investment (FDI) To Domestic Employment Levels in South Africa: A Vector Autoregressive Approach

Abstract: Several empirical works have yielded mixed and controversial results with regard to the effects of FDI on employment and economic growth. The primary focus of this study is to investigate the contribution of FDI to domestic employment levels in the context of the South African economy. The analyses of the study were carried out using the annual time series data from 1980 to 2015. The macroeconomic variables employed in the empirical investigation include employment, FDI, GDP, inflation, trade openness and unit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 12 publications
0
7
1
Order By: Relevance
“…MNCs from other African countries use more domestic labour and transfer more technology than their competitors from developed countries. In the case of South Africa, Makhoba and Kaseeram (2019) provide evidence of a significant negative relationship between FDI and employment levels in the South African economy while stating that FDI focuses on more capital-intensive and tends to sacrifice labour-intensive employment opportunities. Interestingly, they suggest a continuation of FDI incentive schemes for the "purpose of improving other macroeconomic developmental objectives that will create job opportunities" (Makhoba & Kaseeram, 2019, p.119).In Vietnam, the target of a relatively high level of FDI, Anh et al (2008) find evidence of positive backward technological transfers in the manufacturing sector and positive horizontal spillovers in the service sector.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…MNCs from other African countries use more domestic labour and transfer more technology than their competitors from developed countries. In the case of South Africa, Makhoba and Kaseeram (2019) provide evidence of a significant negative relationship between FDI and employment levels in the South African economy while stating that FDI focuses on more capital-intensive and tends to sacrifice labour-intensive employment opportunities. Interestingly, they suggest a continuation of FDI incentive schemes for the "purpose of improving other macroeconomic developmental objectives that will create job opportunities" (Makhoba & Kaseeram, 2019, p.119).In Vietnam, the target of a relatively high level of FDI, Anh et al (2008) find evidence of positive backward technological transfers in the manufacturing sector and positive horizontal spillovers in the service sector.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The effect is strong enough to extinguish any standard positive effects investment has on employment. Many authors have reported the negative relationship from various countries, recipients of FDI, as outlined in the literature review (Ernst, 2005;Jenkins, 2006;Kosztowniak, 2016;Makhoba & Kaseeram, 2019;Nguyen et al, 2020). In general, a weak (negative) relationship between employment and inward FDI is consistent with the political economy of FDI, specifically the OLI paradigm, which explains the additional advantages of MNCs over local companies with "net ownership", "location", and "internalisation".…”
Section: The Oli Paradigmmentioning
confidence: 99%
“…These investors decide independently on whether or not they will enter a certain country. Knickerbocker states that oligopolistic response increases with the level of concentration and decreases with product diversification in the market (Nayak and Choudhury, 2014;Makhoba, 2018). Strategic theory: Since the 1990s, economists have focused increasingly on Company competitiveness (Porter, 1990).…”
Section: Micro Fdi Theoriesmentioning
confidence: 99%
“…FDI theory of gravity: On the other hand, the FDI theory of gravity emphasizes that higher flows of FDI can take place in nations that are relatively close to each other in geographic, economic, and cultural perspectives. According to this theory, the gravity variables can contain the development situation, size, distance, common language, shareholder protection, and openness to foreign investment (Makhoba, 2018;Das, 2007).…”
Section: Macro Fdi Theoriesmentioning
confidence: 99%
See 1 more Smart Citation